Pre-testing of the WHO’s Educational Video: “How to Protect Yourself Against COVID-19” - Fadliyah, Hilyatul; Muhtar, Manendra; Munih, Munih; Risgiantini, Sylviasari; Wulandary, Weny; Pratomo, Hadi (Kesmas, 2020)
The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was declared a public health emergency in many countries, including Indonesia. The World Health Organization (WHO) released an educational video, entitled "How to Protect Yourself Against COVID-19", which explained how to prevent the spread of COVID-19. This study is a qualitative study that aims to pre-test this video, based on the Information, Education, Communication (IEC) theory, by analyzing teenagers’ perceptions of the video. The design used was a Rapid Assessment Procedure (RAP), and the data were collected by conducting in-depth interviews with participants, through virtual meetings. The data were analyzed using a qualitative data matrix and thematic analysis. The results showed that all participants found the video regarding the prevention of COVID-19 spread to be attractive and comprehensible. In addition, the participants felt that the contents of the video were not contradictory to their personal values and that the message was targeted to everyone, including themselves. The video was also perceived to be persuasive. Overall, the participants held a generally positive perception of the video.